An in vitro model of granuloma-like cell aggregates substantiates early host immune responses against Mycobacterium massiliense infection - Je, Sungmo (Biol Open, 2016)
Mycobacterium massiliense (M. mass), belonging to the M. abscessus complex, is a rapidly growing mycobacterium that is known to cause tuberculous-like lesions in humans. To better understand the interaction between host cells and M. mass, we used a recently developed in vitro model of early granuloma-like cell aggregates composed of human peripheral blood mononuclear cells (PBMCs). PBMCs formed granuloma-like, small and rounded cell aggregates when infected by live M. mass. Microscopic examination showed monocytes and macrophages surrounded by lymphocytes, which resembled cell aggregation induced by M. tuberculosis (M. tb). M. mass-infected PBMCs exhibited higher expression levels of HLA-DR, CD86 and CD80 on macrophages, and a significant decrease in the populations of CD4+ and CD8+ T cells. Interestingly, low doses of M. mass were sufficient to infect PBMCs, while active host cell death was gradually induced with highly increased bacterial loads, reflecting host destruction and dissemination of virulent rapid-growing mycobacteria (RGM). Collectively, this in vitro model of M. mass infection improves our understanding of the interplay of host immune cells with mycobacteria, and may be useful for developing therapeutics to control bacterial pathogenesis.